Effect of Hydroxy Propyl Cellulose and Eudragit Polymers on Delayed Release Pellet Systems - Varalakshmi Mummidi; Shaikh Rezwana (Challenges and Advances in Pharmaceutical Research Vol. 5, 2022)
The objective of the present study is to formulate and evaluate omeprazole magnesium delayed release pellets by using drug layering technique with fluid bed processor for the treatment of acidity and ulcers. Solubility studies were carried out by preparing saturated solutions of omeprazole magnesium in various non volatile solvents like methanol, ethanol, acetone, isopropanol and water and also to determine the solubility of drug in the solvents of purified water, pH 6.8 and pH 7.4 phosphate buffers. By adjusting the compositions of drug loading, barrier coating, and enteric coating by employing fluid bed processor, the formulation of delayed release pellets of omeprazole magnesium was developed. The effective release of the medicine takes place in 30 minutes due to the dissolving profile of formulation (F8), which contains an effective amount of hydroxypropyl cellulose-L and eudragit-L30 D55. To demonstrate that the improved formula was not incompatible with the drug and excipients, FTIR and DSC experiments were carried out. To understand the surface morphology of the pellets, SEM investigations were carried out. The enteric polymer eudragit, due to presence of an ester structure, were liable to hydrolysis in humid conditions, affecting the enteric protection in acid medium.